Preparation method of silicon nitride ceramic

By optimizing processes such as tape casting, multi-layer staggered lamination, and sandblasting, the production process of silicon nitride ceramics has been improved, solving the problem of high manufacturing costs, achieving low-cost, high-efficiency large-scale production, and improving the flatness and mechanical properties of the material.

CN119263851AActive Publication Date: 2025-01-07LESHAN VOCATIONAL & TECHN COLLEGE
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411497823.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Silicon nitride ceramics are expensive to manufacture, and existing technologies make it difficult to achieve low-cost and efficient large-scale production. Furthermore, existing improvement methods have limited cost advantages or require large equipment investments, which hinders their widespread application.

Method used

By employing a casting process combined with a multi-layered, alternating stacking method and a one-time sintering process, and utilizing recycled semi-finished products and scraps, the raw material formula and process flow are optimized through the improvement of composite adhesives, sintering aids, and leveling agents, combined with sandblasting treatment, thereby reducing costs and improving production efficiency.

Benefits of technology

This technology enables the low-cost preparation of silicon nitride ceramics, improving the flatness of the material, reducing roughness and warpage, enhancing mechanical properties and production efficiency, and making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101729000000041
    Figure BDA0005101729000000041
  • Figure BDA0005101729000000061
    Figure BDA0005101729000000061
  • Figure BDA0005101729000000081
    Figure BDA0005101729000000081
Patent Text Reader

Abstract

The invention discloses a preparation method of silicon nitride ceramic. The preparation method comprises the steps of organic glue preparation, recycled slurry treatment, recycled material treatment, ball milling and mixing, defoaming and aging, tape casting, blanking and isolation powder application, air glue discharging, pressure sintering and sand blasting treatment. The prepared silicon nitride substrate is good in flatness, low in roughness and high in mechanical property. The acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester composite adhesive is adopted, so that the fracture toughness of the material is improved; the ytterbium fluoride and strontium hexaboride composite sintering aid is adopted, so that the roughness of the material is reduced; organic silicon fluorine and a BYK-3902P composite flatting agent are adopted, so that the warping degree of the material is reduced, and the smoothness of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon nitride ceramic preparation, and particularly relates to a method for preparing silicon nitride ceramic. Background Art

[0002] Silicon nitride ceramics have many advantages such as high strength, high hardness, high thermal conductivity, low thermal expansion coefficient, low high temperature creep, good oxidation resistance, good thermal corrosion resistance, low friction coefficient, etc. They have an irreplaceable position in key fields such as national defense, military industry, and electronic information. However, due to the large equipment investment and high manufacturing cost of silicon nitride ceramics, its large-scale application is limited, so that it can only be used in the high-end field of automotive IGBT.

[0003] To further expand the application of silicon nitride ceramics, the key is to use efficient large-scale production equipment and significantly reduce the manufacturing cost through various methods. Therefore, it is particularly important to study a low-cost and large-scale production technology for silicon nitride ceramics.

[0004] The cost of silicon nitride ceramics is mainly concentrated on the production efficiency and qualified rate of the molding and sintering processes of raw and auxiliary materials including silicon nitride powder and equipment investment. First of all, in the manufacturing process of aluminum nitride ceramics, many semi-finished products will inevitably be produced in each process due to equipment and process reasons. The semi-finished products before sintering can be reused equivalent to new powder after reasonable treatment by certain methods and will not affect the performance of the final product. This kind of semi-finished product treatment will greatly reduce the input of new powder and thus reduce the manufacturing cost. Secondly, the molding adopts the highly efficient tape casting molding process, which can achieve continuous large-scale production while ensuring high production efficiency. Finally, the sintering adopts a multi-layer positive and negative staggered stacking method and a one-time sintering porcelain process, which can make full use of the effective volume of the kiln sintering and reduce the pre-sintering process, which plays a significant role in reducing the manufacturing cost. However, the reuse of new powder will also cause the performance of the final material to decrease, and the raw material formula or process needs to be optimized.

[0005] 201310241572.4 discloses a method for producing low-cost silicon nitride ceramics. The patent only mentions the use of cheap monazite to replace cerium oxide and lanthanum oxide, and the proportion of flux added is only 6-9wt%, and the cost reduction is very limited. Patent 201910323311.4 discloses a method for preparing low-cost silicon nitride ceramics. The solvent used is analytically pure anhydrous ethanol, spray drying and granulation are required, and the molding adopts isostatic pressing that cannot be produced continuously and has low efficiency. It is necessary to pre-sinter at 800-1400 degrees and other materials and processes, and the cost advantage is not obvious. Patent 202080011345.0 discloses a method for manufacturing a single green sheet, a method for manufacturing a silicon nitride sintered body, a single green sheet and a silicon nitride sintered body. The green body is processed by laser cutting, which is not only inefficient, but also requires large equipment investment, which is not conducive to mass production. Patent 201910223395.4 discloses a method for producing high-strength and high-thermal-conductivity silicon nitride substrates. After sintering, additional machining is used to process the surface of the substrate by surface polishing, which adds a process step and increases costs. Patent 202011118907.X discloses a high-thermal-conductivity silicon nitride ceramic substrate and a preparation method thereof. This method requires high-temperature preheating at 1200-1500°C and then high-temperature sintering at 1750-1950°C, which reduces the efficiency of the most expensive equipment furnace and adds a heating process, increasing costs. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing silicon nitride ceramics.

[0007] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0008] (1) preparing organic glue: adding adhesive, plasticizer and organic solvent into a container and stirring evenly; the mass ratio of the adhesive, plasticizer and organic solvent is (15-25): (10-20): (80-120);

[0009] (2) Recycled slurry treatment: add an organic solvent to the slurry remaining from each process before casting, add it to a container and stir it evenly, the mass ratio of the recycled slurry to the organic solvent is (30-50): (10-20);

[0010] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and organic solvent into the ball mill at a mass ratio of (10-20): (10-20): (30-50), and ball mill for 24-48 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0011] (4) ball milling and mixing: adding organic solvent, silicon nitride powder, recycling slurry, recycled material, sintering aid, dispersant and leveling agent to a ball mill in sequence, and ball milling for 12-24 hours to obtain a mixed slurry; adding the organic glue prepared in step (1), and ball milling for another 24-36 hours to obtain a casting slurry; the mass ratio of the organic solvent, silicon nitride powder, recycling slurry, recycled material, sintering aid, dispersant and leveling agent is (90-130): (60-120): (20-30): (20-30): (5-15): (5-10): (5-15); the mass ratio of the mixed slurry to the organic glue is (1-5): 1;

[0012] (5) Degassing and aging: vacuum degassing the tape casting slurry prepared in step (4) for 10-30 min, and stirring and aging at a speed of 5-10 rpm for 10-15 h, controlling the viscosity to be 6000-20000 cps, the solid content to be 55-75%, and the temperature to be 10-25° C.;

[0013] (6) Tape casting: The slurry prepared in step (5) is tape-casted using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.1-0.2 m / min, the temperature of the first zone of the tape casting drying chamber is 15-35° C., the temperature of the second zone of the tape casting drying chamber is 55-85° C., and the temperature of the third zone of the tape casting drying chamber is 70-110° C.;

[0014] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to the powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.05-0.1Mpa and the powder coating temperature is 55-85°C;

[0015] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 450-650°C, total time: 15-25h, heating rate <5°C / min between 220-350°C;

[0016] (9) Pressure sintering: Place the debinded product into a sintering furnace for sintering; process parameters of this step: sintering temperature 1650-1850°C, sintering time: 15-25h, pressure: 0.5-1.0Mpa;

[0017] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic.

[0018] The adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of (1-5):1.

[0019] The plasticizer is one or more of methyl phthalate, di(2-ethylhexyl) terephthalate, dibutyl sebacate, and di(2-ethylhexyl) cyclohexane-1,4-dicarboxylate.

[0020] The organic solvent is one or more of toluene, xylene, isopropanol, ethanol and ethyl acetate.

[0021] The sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of (1-3):1.

[0022] The dispersant is one or more of polyethyleneimine, ammonium citrate, ammonium persulfate, sodium tripolyphosphate, tetraethylethylenediamine, ammonium acrylate, trioleylglycerol, and phosphate.

[0023] The leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:(1-3); the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0024]

[0025] The raw material components and proportions of the isolation powder in step (7) are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1: (0.015-0.025): (3-5).

[0026] The sandblasting in step (10): sand types: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 100-3000 mesh; pressure = 0.01-0.5Mpa.

[0027] Beneficial effects of the present invention: The silicon nitride substrate prepared by the present invention has good flatness, low roughness and high mechanical properties. The composite adhesive of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester is used to improve the fracture toughness of the material; the composite sintering aid of ytterbium fluoride and strontium hexaboride is used to reduce the roughness of the material; the composite leveling agent of organic silicon fluorine and BYK-3902P is used to reduce the warpage of the material and improve the flatness of the material. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] Example 1

[0030] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0031] (1) preparing an organic glue: adding an adhesive, methyl phthalate, and ethanol into a container and stirring the mixture evenly; the mass ratio of the adhesive, methyl phthalate, and ethanol is 20:15:100; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 3:1;

[0032] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0033] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0034] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent are added to a ball mill in sequence and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 2:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:2; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0035]

[0036] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0037] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0038] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0039] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0040] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0041] (10) Sand blasting: using sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic, wherein the sand blasting includes: alumina, zirconia, silicon dioxide, with a mass ratio of 1:1:1; grit number: 800 mesh; and pressure = 0.03 MPa.

[0042] Example 2

[0043] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0044] (1) preparing an organic glue: adding an adhesive, di(2-ethylhexyl) terephthalate, and xylene into a container and stirring the mixture evenly; the mass ratio of the adhesive, di(2-ethylhexyl) terephthalate, and xylene is 15:11:85; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 1:1;

[0045] (2) Recycled slurry treatment: Add xylene to the slurry remaining from each process before casting, add it into a container and stir evenly, the mass ratio of the recycled slurry to xylene is 30:11;

[0046] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and xylene into the ball mill at a mass ratio of 10:10:32, and ball mill for 24 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0047] (4) Ball milling and mixing: xylene, silicon nitride powder, recycled slurry, recycled material, sintering aid, tetraethylethylenediamine, and leveling agent are added to a ball mill in sequence, and ball milled for 12 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and ball milled for another 24 hours to obtain a casting slurry; the mass ratio of the xylene, silicon nitride powder, recycled slurry, recycled material, sintering aid, tetraethylethylenediamine, and leveling agent is 90:60:20:20:5:5:5; the mass ratio of the mixed slurry to the organic glue is 1:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 1:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:1; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0048]

[0049] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 10 min, and stirred and aged for 10 h at a speed of 5 rpm, with the viscosity controlled at 8000 cps, the solid content at 55%, and the temperature at 10°C;

[0050] (6) Tape casting: The slurry prepared in step (5) is tape-casted using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.1 m / min, the temperature of the first zone of the tape casting drying chamber is 15° C., the temperature of the second zone of the tape casting drying chamber is 55° C., and the temperature of the third zone of the tape casting drying chamber is 70° C.;

[0051] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.05 MPa and the powder coating temperature is 55° C. The raw material components and ratio of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.015:3;

[0052] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 450°C, total time: 15h, heating rate at 220°C <5°C / min;

[0053] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1650°C, sintering time: 15h, pressure: 0.5Mpa;

[0054] (10) Sand blasting: using sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic, wherein the sand blasting includes: alumina, zirconia, silicon dioxide, with a mass ratio of 1:1:1; grit number: 500 mesh; and pressure = 0.03 MPa.

[0055] Example 3

[0056] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0057] (1) preparing an organic glue: adding an adhesive, di(2-ethylhexyl) cyclohexane-1,4-dicarboxylate, and ethyl acetate into a container and stirring evenly; the mass ratio of the adhesive, di(2-ethylhexyl) cyclohexane-1,4-dicarboxylate, and ethyl acetate is 25:20:120; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 4:1;

[0058] (2) Recycled slurry treatment: Add ethyl acetate to the slurry remaining from each process before casting, add it into a container and stir evenly, the mass ratio of the recycled slurry to ethyl acetate is 50:20;

[0059] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethyl acetate in a mass ratio of 20:20:50 into a ball mill, mill for 48 hours, and use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0060] (4) Ball milling and mixing: ethyl acetate, silicon nitride powder, recycled slurry, recycled material, sintering aid, sodium tripolyphosphate, and leveling agent are added to a ball mill in sequence, and ball milled for 24 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and ball milled for another 36 hours to obtain a casting slurry; the mass ratio of the ethyl acetate, silicon nitride powder, recycled slurry, recycled material, sintering aid, sodium tripolyphosphate, and leveling agent is 130:120:30:30:15:10:15; the mass ratio of the mixed slurry to the organic glue is 4:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 3:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:3; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0061]

[0062] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 30 min, and stirred and aged for 15 h at a speed of 10 rpm, with the viscosity controlled at 20,000 cps, the solid content at 75%, and the temperature at 25° C.;

[0063] (6) Tape casting: The slurry prepared in step (5) is tape cast using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.2 m / min, the temperature of the first zone of the tape casting drying chamber is 35° C., the temperature of the second zone of the tape casting drying chamber is 85° C., and the temperature of the third zone of the tape casting drying chamber is 110° C.;

[0064] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.1 MPa and the powder coating temperature is 85° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.025:5;

[0065] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 650°C, total time: 25h, heating rate <5°C / min at 300°C;

[0066] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1850°C, sintering time: 25h, pressure: 1.0Mpa;

[0067] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 1.2 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 2500 mesh; pressure = 0.45 MPa.

[0068] Comparative Example 1

[0069] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0070] (1) preparing organic glue: adding acrylonitrile-butadiene-styrene copolymer, methyl phthalate and ethanol into a container and stirring evenly; the mass ratio of the acrylonitrile-butadiene-styrene copolymer, methyl phthalate and ethanol is 20:15:100;

[0071] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0072] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0073] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent are added to a ball mill in sequence and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 2:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:2; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0074]

[0075] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0076] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0077] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0078] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0079] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0080] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 0.6 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0081] Comparative Example 2

[0082] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0083] (1) preparing organic glue: adding polyaspartic acid ester, methyl phthalate and ethanol into a container and stirring evenly; the mass ratio of the polyaspartic acid ester, methyl phthalate and ethanol is 20:15:100;

[0084] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0085] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0086] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent are added to a ball mill in sequence and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 2:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:2; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0087]

[0088] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0089] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0090] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0091] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0092] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0093] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 0.6 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0094] Comparative Example 3

[0095] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0096] (1) preparing an organic glue: adding an adhesive, methyl phthalate, and ethanol into a container and stirring the mixture evenly; the mass ratio of the adhesive, methyl phthalate, and ethanol is 20:15:100; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 3:1;

[0097] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0098] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0099] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycling slurry, recycled material, ytterbium fluoride, polyethyleneimine, and leveling agent are added to a ball mill in sequence, and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycling slurry, recycled material, ytterbium fluoride, polyethyleneimine, and leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:2; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0100]

[0101] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0102] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0103] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0104] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0105] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0106] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 0.6 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0107] Comparative Example 4

[0108] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0109] (1) preparing an organic glue: adding an adhesive, methyl phthalate, and ethanol into a container and stirring the mixture evenly; the mass ratio of the adhesive, methyl phthalate, and ethanol is 20:15:100; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 3:1;

[0110] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0111] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0112] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycling slurry, recycled material, strontium hexaboride, polyethyleneimine, and a leveling agent are added to a ball mill in sequence, and the mixture is ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and the mixture is ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycling slurry, recycled material, strontium hexaboride, polyethyleneimine, and a leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:2; the molecular structure of the organic silicon fluorine leveling agent is as follows:

[0113]

[0114] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0115] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0116] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0117] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0118] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0119] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 0.6 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0120] Comparative Example 5

[0121] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0122] (1) preparing an organic glue: adding an adhesive, methyl phthalate, and ethanol into a container and stirring the mixture evenly; the mass ratio of the adhesive, methyl phthalate, and ethanol is 20:15:100; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 3:1;

[0123] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0124] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0125] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent are added to a ball mill in sequence, and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 2:1; the leveling agent is an organic silicon fluorine leveling agent, and the molecular structure is as follows:

[0126]

[0127] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0128] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0129] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0130] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0131] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0132] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements, with a roughness of Ra = 0.6 um; the sand blasting: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0133] Comparative Example 6

[0134] A method for preparing silicon nitride ceramics is carried out according to the following steps:

[0135] (1) preparing an organic glue: adding an adhesive, methyl phthalate, and ethanol into a container and stirring the mixture evenly; the mass ratio of the adhesive, methyl phthalate, and ethanol is 20:15:100; the adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of 3:1;

[0136] (2) Recycled slurry treatment: add ethanol to the slurry remaining from each process before casting, add it into a container and stir it evenly, the mass ratio of the recycled slurry to ethanol is 40:15;

[0137] (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and ethanol into the ball mill at a mass ratio of 15:15:40, and ball mill for 36 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket;

[0138] (4) Ball milling and mixing: ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and BYK-3902P leveling agent are added to a ball mill in sequence, and ball milled for 18 hours to obtain a mixed slurry; the organic glue prepared in step (1) is added, and ball milled for another 28 hours to obtain a casting slurry; the mass ratio of the ethanol, silicon nitride powder, recycled slurry, recycled material, sintering aid, polyethyleneimine, and BYK-3902P leveling agent is 110:80:25:25:10:8:10; the mass ratio of the mixed slurry to the organic glue is 3:1; the sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of 2:1;

[0139] (5) Degassing and aging: The casting slurry prepared in step (4) was subjected to vacuum degassing for 20 min, and stirred and aged for 12 h at a speed of 8 rpm, with the viscosity controlled at 10,000 cps, the solid content at 65%, and the temperature at 18°C;

[0140] (6) Tape casting: The slurry prepared in step (5) is subjected to tape casting using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.15 m / min, the temperature of the first zone of the tape casting drying chamber is 25° C., the temperature of the second zone of the tape casting drying chamber is 65° C., and the temperature of the third zone of the tape casting drying chamber is 90° C.;

[0141] (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to a powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.08 MPa and the powder coating temperature is 65° C. The raw material components and ratios of the isolation powder are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1:0.02:4;

[0142] (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 500°C, total time: 20h, heating rate <5°C / min at 280°C;

[0143] (9) Pressure sintering: the debinded product is placed in a sintering furnace for sintering; the process parameters of this step are: sintering temperature 1750°C, sintering time: 20h, pressure: 0.8Mpa;

[0144] (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic. At the same time, the sand blasting equipment performs sand blasting on the product surface according to customer requirements. The sand blasting includes: sand type: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 800 mesh; pressure = 0.03 MPa.

[0145] Experimental Example 1:

[0146] The fracture toughness of the silicon nitride substrates prepared in Examples 1-3 and Comparative Examples 1-2 was tested by indentation method, the applied load was 196N, each group of experiments was measured three times in parallel, and SPSS24.0 software was used for statistical analysis. The quantitative data results were expressed as The data were expressed as mean ± standard deviation. The Kolmogorov-Smirnov test was used for normality test. For data that met the normal distribution, the t-test was used to compare the mean differences between the two groups. The difference was considered statistically significant when P < 0.05.

[0147] The test results are shown in Table 1:

[0148] Table 1

[0149]

[0150]

[0151] Note: * represents P < 0.05 compared with the group in Example 1.

[0152] Experimental Example 2:

[0153] The surface roughness of the silicon nitride substrates prepared in Examples 1-3 and Comparative Examples 3-4 was tested. The surface roughness was tested by selecting at least 5 test points on the front and back sides of the silicon nitride substrate, and taking the average value of the roughness of all the test points as the test result. All the test points include a central point located in the center, and the remaining test points are located outside the central point and close to the corners of the silicon nitride substrate. The test results are shown in Table 2:

[0154] Table 2

[0155]

[0156] Note: * represents P < 0.05 compared with the group in Example 1.

[0157] Experimental Example 3:

[0158] The warpage (mm / 25.4 mm) of the silicon nitride substrates prepared in Examples 1-3 and Comparative Examples 5-6 was tested. The test results are shown in Table 3:

[0159] Table 3

[0160]

[0161]

[0162] Note: * represents P < 0.05 compared with the group in Example 1.

[0163] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing silicon nitride ceramics, characterized in that: Follow these steps: (1) preparing organic glue: adding adhesive, plasticizer and organic solvent into a container and stirring evenly; the mass ratio of the adhesive, plasticizer and organic solvent is (15-25): (10-20): (80-120); (2) Recycled slurry treatment: add an organic solvent to the slurry remaining from each process before casting, add it to a container and stir it evenly, the mass ratio of the recycled slurry to the organic solvent is (30-50): (10-20); (3) Recycled material treatment: Add the scraps from tape casting and pressure sintering, green waste and organic solvent into the ball mill at a mass ratio of (10-20): (10-20): (30-50), and ball mill for 24-48 hours. Use a device with a multi-stage filter to discharge the material from the ball mill into a clean bucket; (4) ball milling and mixing: adding organic solvent, silicon nitride powder, recycling slurry, recycled material, sintering aid, dispersant and leveling agent to a ball mill in sequence, and ball milling for 12-24 hours to obtain a mixed slurry; adding the organic glue prepared in step (1), and ball milling for another 24-36 hours to obtain a casting slurry; the mass ratio of the organic solvent, silicon nitride powder, recycling slurry, recycled material, sintering aid, dispersant and leveling agent is (90-130): (60-120): (20-30): (20-30): (5-15): (5-10): (5-15); the mass ratio of the mixed slurry to the organic glue is (1-5): 1; (5) Degassing and aging: vacuum degassing the tape casting slurry prepared in step (4) for 10-30 min, and stirring and aging at a speed of 5-10 rpm for 10-15 h, controlling the viscosity to be 6000-20000 cps, the solid content to be 55-75%, and the temperature to be 10-25° C.; (6) Tape casting: The slurry prepared in step (5) is tape-casted using a tape casting machine, and the green body is wrapped with a paper tube; the process parameters of this step are: tape casting speed 0.1-0.2 m / min, the temperature of the first zone of the tape casting drying chamber is 15-35° C., the temperature of the second zone of the tape casting drying chamber is 55-85° C., and the temperature of the third zone of the tape casting drying chamber is 70-110° C.; (7) Punching and applying isolation powder: Select a punching die according to the drawing requirements, cut the green blank prepared in step (6), and transport it to the powder coating line via a conveyor belt for powder coating. The powder coating pressure is 0.05-0.1Mpa and the powder coating temperature is 55-85°C; (8) Air debinding: Place the flattened green body into an intermittent furnace for debinding; process parameters of this step: debinding temperature 450-650°C, total time: 15-25h, heating rate <5°C / min between 220-350°C; (9) Pressure sintering: Place the debinded product into a sintering furnace for sintering; process parameters of this step: sintering temperature 1650-1850°C, sintering time: 15-25h, pressure: 0.5-1.0Mpa; (10) Sand blasting: Use sand blasting equipment to remove the isolation powder on the surface of the sintered silicon nitride ceramic.

2. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The adhesive is a mixture of acrylonitrile-butadiene-styrene copolymer and polyaspartic acid ester in a mass ratio of (1-5):

1.

3. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The plasticizer is one or more of methyl phthalate, di(2-ethylhexyl) terephthalate, dibutyl sebacate, and di(2-ethylhexyl) cyclohexane-1,4-dicarboxylate.

4. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The organic solvent is one or more of toluene, xylene, isopropanol, ethanol and ethyl acetate.

5. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The sintering aid is a mixture of ytterbium fluoride and strontium hexaboride in a mass ratio of (1-3):

1.

6. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The dispersant is one or more of polyethyleneimine, ammonium citrate, ammonium persulfate, sodium tripolyphosphate, tetraethylethylenediamine, ammonium acrylate, trioleylglycerol, and phosphate.

7. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The leveling agent is a mixture of an organic silicon fluorine leveling agent and a BYK-3902P leveling agent in a mass ratio of 1:(1-3); the molecular structure of the organic silicon fluorine leveling agent is as follows:

8. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The raw material components and proportions of the isolation powder in step (7) are: boron nitride powder: polyvinyl butyral: anhydrous ethanol = 1: (0.015-0.025): (3-5).

9. The method for preparing silicon nitride ceramics according to claim 1, characterized in that: The sandblasting in step (10): sand types: alumina, zirconia, silicon dioxide, mass ratio 1:1:1; sand mesh number: 100-3000 mesh; pressure = 0.01-0.5Mpa.

Citation Information

Patent Citations

  • Production method for high-strength high-thermal-conduction silicon nitride substrate

    CN109851370A

  • Preparation method of low-cost silicon nitride ceramic

    CN109942301A

  • High-thermal-conductivity silicon nitride ceramic substrate and preparation method thereof

    CN112159236A

  • Method for manufacturing single sheet-type green sheet, method for manufacturing silicon nitride sintered body, single sheet-type green sheet and silicon nitride sintered body

    CN113508016A

  • Polyurea paint formula and polyurea paint prepared by polyurea paint formula

    CN103436148A